Cough Is Dangerous: Neural Correlates of Implicit Body Symptoms Associations - Mier, Daniela; Witthöft, Michael; Bailer, Josef; Ofer, Julia; Kerstner, Tobias; Rist, Fred; Diener, Carsten (Frontiers in Psychology, 2016)
The negative interpretation of body sensations (e.g., as sign of a severe illness) is a crucial cognitive process in pathological health anxiety (HA). However, little is known about the nature and the degree of automaticity of this interpretation bias. We applied an implicit association test (IAT) in 20 subjects during functional magnetic resonance imaging (fMRI) to investigate behavioral and neural correlates of implicit attitudes towards symptom words. On the behavioral level, body symptom words elicited strong negative implicit association effects, as indexed by slowed reaction times when symptom words were paired with the attribute “harmless” (incongruent condition) relative to a control condition. fMRI revealed increased activation in the dorsolateral prefrontal cortex and posterior parietal cortex for the comparison of incongruent words with control words, as well as with a lower significance threshold also in comparison to congruent words. Moreover, activation in the dorsolateral prefrontal cortex, posterior parietal cortex, nucleus accumbens, and cerebellum varied with individual levels of HA (again, in comparison to control words, as well as with a lower significance threshold also in comparison to congruent words). Slowed reaction times as well as increased activation in dorsolateral prefrontal and posterior parietal cortex point to increased inhibitory demands during the incongruent IAT condition. The positive association between HA severity and neural activity in nucleus accumbens, dorsolateral prefrontal, and posterior parietal cortex suggests that HA is characterized by both intensified negative implicit attitudes and hampered cognitive control mechanisms when confronted with body symptoms.